SCIMP, a transmembrane adaptor protein involved in major histocompatibility complex class II signaling - Draber, Peter; Vonkova, Ivana; Stepanek, Ondrej; Hrdinka, Matous; Kucova, Marketa; Skopcova, Tereza; Otahal, Pavel; Angelisova, Pavla; Horejsi, Vaclav; Yeung, Mandy; Weiss, Arthur; Brdicka, Tomas (Molecular and cellular biology, 2011)
Formation of the immunological synapse between an antigen-presenting cell (APC) and a T cell leads to signal generation in both cells involved. In T cells, the lipid raft-associated transmembrane adaptor protein LAT plays a central role. Its phosphorylation is a crucial step in signal propagation, including the calcium response and mitogen-activated protein kinase activation, and largely depends on its association with the SLP76 adaptor protein. Here we report the discovery of a new palmitoylated transmembrane adaptor protein, termed SCIMP. SCIMP is expressed in B cells and other professional APCs and is localized in the immunological synapse due to its association with tetraspanin-enriched microdomains. In B cells, it is constitutively associated with Lyn kinase and becomes tyrosine phosphorylated after major histocompatibility complex type II (MHC-II) stimulation. When phosphorylated, SCIMP binds to the SLP65 adaptor protein and also to the inhibitory kinase Csk. While the association with SLP65 initiates the downstream signaling cascades, Csk binding functions as a negative regulatory loop. The results suggest that SCIMP is involved in signal transduction after MHC-II stimulation and therefore serves as a regulator of antigen presentation and other APC functions.
Keywords: src-Family Kinases; Protein-Tyrosine Kinases; T-Lymphocytes; tyrosinkinasy; C-terminální Src kinasa; Membrane Microdomains; RNA interference; Amino Acid Sequence; Lymphocyte Activation; fosfoproteiny; Mitogen-Activated Protein Kinases; molekulární sekvence - údaje; membránové mikrodomény; RNA, Small Interfering; Humans; B-lymfocyty; Molecular Sequence Data; skupina kinas odvozených od src-genu; sekvence aminokyselin; MHC antigeny II. třídy; Adaptor Proteins, Signal Transducing; CSK Tyrosine-Protein Kinase; mitogenem aktivované proteinkinasy; RNA Interference; Antigen-Presenting Cells; Phosphoproteins; malá interferující RNA; aktivace lymfocytů; imunologické synapse; Immunological Synapses; Membrane Proteins; src Homology Domains; membránové proteiny; Histocompatibility Antigens Class II; adaptorové proteiny signální transdukční; B-Lymphocytes; antigen prezentující buňky; HEK293 Cells; src homologní domény; lidé; HEK293 buňky; T-lymfocyty; Signal Transduction; prezentace antigenu; Antigen Presentation; signální transdukce